2021
DOI: 10.1016/j.virol.2021.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of FOXP3 is associated with severity of hypoxia and poor outcomes in COVID-19 patients

Abstract: The levels of messenger RNA (mRNA) transcription of FOXP3, IFN-γ, TNF, IL-6 and COX-2 from both COVID-19 infected and control subjects were evaluated using SYBR TM green real-time polymerase chain reaction (RT-PCR). Severe/critical cases showed significantly lower lymphocyte counts and higher neutrophil counts than the mild or moderate cases. There were significantly lower levels of mRNA expressions of IFN-γ, TNFα and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…COVID-19 is associated with immune dysregulation, which is related to the severity of the disease [ 27 ]. Restoration of baseline and homeostasis after COVID-19 needs some time, which is expected to be longer in severe forms of the diseases.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is associated with immune dysregulation, which is related to the severity of the disease [ 27 ]. Restoration of baseline and homeostasis after COVID-19 needs some time, which is expected to be longer in severe forms of the diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the present study's findings, Abdelhafiz et al discovered a significant decrease in FOXP3 in COVID-19 patients, suggesting that immunological dysregulation in COVID-19 patients is one of the consequences of this shift. Abdelhafiz et al also discovered that FOXP3 is a favorable predictive factor in individuals with severe symptoms and is elevated in these patients, resulting in hypoxia, which can lead to ARDS (30). In a study by Rezaei et al, no significant changes were observed in the FOXP3 expression level throughout the first week of the sickness.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, FoxP3, which improves the expansion of Treg cells’ function is severely downregulated in SARS-CoV-2 infection and coincides with COVID-19 severity [ 88 ]. Mohebbi et al study revealed that FoxP3 might be a potential biomarker for the assessment of COVID-19 severity [ 89 ].…”
Section: Role Of Neuropilin-1 In Covid-19mentioning
confidence: 99%